Dual-process theories of the social mind - Sherman, Jeffrey W.; Gawronski, Bertram; Trope, Yaacov (The Guilford Press, 2014)
"Subject Areas/Keywords: attitudes, automatic processes, cognitive, controlled processes, dual-process, dual-systems, information processing, measurement, measures, mind, models, self-regulation, social cognition, social perception, social psychology, theories, unconscious Description: This volume provides an authoritative synthesis of a dynamic, influential area of psychological research. Leading investigators address all aspects of dual-process theories: their core assumptions, conceptual foundations, and applications to a wide range of social phenomena. In 38 chapters, the volume addresses the pivotal role of automatic and controlled processes in attitudes and evaluation; social perception; thinking and reasoning; self-regulation; and the interplay of affect, cognition, and motivation. Current empirical and methodological developments are described. Critiques of the duality approach are explored and important questions for future research identified. "--
Includes bibliographical references and indexes
Keywords: Aufsatzsammlung; Zwei-Prozess-Modell; Sozialpsychologie